The Role of Al Banjari Hadroh Activities in Fostering Students' Love for Islamic Arts in Islamic Boarding Schools - Sugiyanto, Sugiyanto; Zamroji, Muhammad; Refa , Muhammad Fadhlan (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2025)
This article aims to analyse the role of hadroh extracurricular activities in fostering students' love for Islamic arts and to identify the supporting and inhibiting factors in its implementation at the Nurul Ahmadi Islamic Boarding School in Jombang. The research focuses on how hadroh functions not only as a means of entertainment but also as a medium for worship, preaching, and character building for students. This research uses a descriptive qualitative approach with a field study design. Data was collected through observation, in-depth interviews with caregivers, coaches, and students, as well as documentation of hadroh activities. Data validity was tested using source, technique, and time triangulation techniques, while data analysis was carried out using an interactive model of reduction, presentation, and conclusion drawing.The results of the study indicate that hadroh activities play a strategic role in fostering students' love for Islamic arts through strengthening spirituality, instilling discipline and responsibility, developing Islamic artistic talents, and reinforcing Islamic cultural identity. The main supporting factors include the support of caregivers, the availability of facilities, and the solidarity of students, while the inhibiting factors are the busy academic schedule and the limited number of professional trainers. The contribution of this article lies in confirming previous findings regarding the function of hadroh as a medium for religious guidance, while also contributing a new perspective by emphasising its role as an instrument of cultural da'wah and a means of preserving Islamic cultural identity in Islamic boarding schools. Thus, this article enriches the study of the integration of Islamic arts in Islamic boarding school education.